Desenvolvimento da versão em português do Nutriscore - Mendes, J. (2020)
Nutriscore is the only nutritional screening tool developed specifically for oncological outpatients. Due to the absence of a Portuguese version, the aim of this study was to create a Portuguese validated translation. The ten steps of the International Society for Pharmacoeconomics and Outcomes Research guideline were followed: preparation, forward translation, reconciliation, back translation, back translation review, harmonization, cognitive debriefing, review of the cognitive debriefing results and finalization, proofreading and final report. The screening tool was applied to 46 oncological outpatients by six health care providers. It can be concluded that the Portuguese version of Nutriscore maintains the concepts and equivalence of the original tool, is easy to understand and apply, with good acceptability and face validity. This version will be useful for determining the risk of undernutrition in outpatient oncological patients in Portugal and eventually in other settings where the Portuguese language is used.